Beyond ’Where do you really come from?’: : Rethinking positionality and racial dynamics in Nordic exceptionalism - Gobena, Eden Begna; Dickstein, Joshua D.; Zeleke, Girum; Dansholm, Kerenina Kezaride (Reconceptualizing Educational Research Methodology, 2025)
Engaging with the complex dynamics of positionality, racialisation, and social demarcation, this study situates itself at the intersection of critical race theory (CRT) and understandings of reflexivity and positionality. It aims specifically to challenge and expand traditional understandings of ‘positionality’, which have largely centred on introspective concerns, such as how researchers’ individual experiences influence their methodological choices. As such, the paper argues for a more nuanced application of positionality, beginning from the Nordic exceptionalist post-colonial context where the societal self-perception is that Nordic countries are free of colonial legacies and uniquely progressive and egalitarian. To this end, the study employs a reflexive methodology deeply rooted in the authors’ own intersectional lived experiences. The paper critically engages with the potent, yet often unspoken question, frequently posed to people of colour in Nordic countries: ‘Where do you really come from?’ This intrusive curiosity is not just one of geographic origin but is intricately tied to perceived racialised positionality (PRP), highlighting a clear connection between the question and assumptions about identity and belonging. Furthermore, the query serves as a mechanism of social demarcation that separates ‘us,’ the presumed native Nordics, from ‘them,’ the racialised ‘Other.’ By focusing on this divisive question, the paper aims to dissect the social, ethical, and methodological implications of ‘perceived racialised positionality’ (PRP) – a term which captures the essence of how others’ perceptions of our racial identity can influence teaching and research specifically, and more generally processes and outcomes of scholarly enrichment of the ethical and intellectual landscape in Nordic settings and beyond. The paper critically engages with the potent, yet often unspoken question, frequently posed to people of colour in Nordic countries: ‘Where do you really come from?’ This intrusive curiosity is not just one of geographic origin but is intricately tied to perceived racialised positionality (PRP), highlighting a clear connection between the question and assumptions about identity and belonging. Furthermore, the query serves as a mechanism of social demarcation that separates ‘us,’ the presumed native Nordics, from ‘them,’ the racialised ‘Other.’ By focusing on this divisive question, the paper aims to dissect the social, ethical, and methodological implications of ‘perceived racialised positionality’ (PRP) – a term which captures the essence of how others’ perceptions of our racial identity can influence teaching and research specifically, and more generally processes and outcomes of scholarly enrichment of the ethical and intellectual landscape in Nordic settings and beyond.